(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Gastrointestinal symptoms are relatively common in clinical practice in patients with type II diabetes mellitus. type II DM has been described as possible risk factor for the development of gastroesophageal reflux disease, in this study we aim to detect the prevalence of GRED in symptomatic patients with type II DM , also to see the accuracy of reflex disease questionnaire ( RDQ) in the diagnosis of GERD in patients with type II DM in relation to the esophagogastroduodenoscopy finding and to study the relation of autonomic neuropathy to the prevalence and stages of GERD in diabetic patients . Methods: A ninety patients with upper gastrointestinal symptoms was divided in to tow groups according to whether had type II DM or not and then each group involved in a two stage process (a ) – a RDQ , ( b ) – OGD . And patients in the DM group underwent another step to detect diabetic neuropathy by a bed side clinical test. Results: The prevalence of esophagitis in this study was higher in the DM group. RDQ had a statistical significance in detecting esophagitis in the DM group. There is no relation of autonomic neuropathy to the prevalence of GERD in diabetic patients . Conclusion : The prevalence of GERD was high in patients with type II DM, RDQ is a sensitive tool for the diagnosis of GERD in diabetic pateints , Autonomic neuropathy did not increase prevalence of esophagitis in diabetic patients .